2014 21st International Conference on Telecommunications (ICT) 2014
DOI: 10.1109/ict.2014.6845155
|View full text |Cite
|
Sign up to set email alerts
|

Empirical investigation on the dependence of TCP upstream throughput on SNR in an IEEE802.11b WLAN system

Abstract: An empirical investigation on the dependence of TCP upstream throughput against signal to noise ratio (SNR) in an IEEE802.11b WLAN system was carried out in various environments and varieties of QoS traffic. The TCP upstream throughput (TCP up T) was measured for various SNR observed. An Infrastructure based IEEE802.11b WLAN system having networked computers on which measurement software were installed, was set up consecutively in various environments (open corridor, small offices with block walls and plaster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The method used in Oghogho, et al, (2014a), Oghogho et al, (2014b) and Oghogho (2019) was also used in this work except that RTT multiple users data was collected instead of throughput data. The multiple users RTT data collected were categorized into four categories using the SNR namely: (i) All signals considered, (ii) Strong signals only (SNR>25dB), (iii) Grey signals only (25dB>SNR>18dB) (iv) Weak signals only (SNR<19dB) only.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method used in Oghogho, et al, (2014a), Oghogho et al, (2014b) and Oghogho (2019) was also used in this work except that RTT multiple users data was collected instead of throughput data. The multiple users RTT data collected were categorized into four categories using the SNR namely: (i) All signals considered, (ii) Strong signals only (SNR>25dB), (iii) Grey signals only (25dB>SNR>18dB) (iv) Weak signals only (SNR<19dB) only.…”
Section: Methodsmentioning
confidence: 99%
“…Several research has shown that throughput in WLANs can be predicted directly from the SNR with reasonable accuracy (Henty, (2001); Oghogho et al, (2014a); Oghogho et al, (2014b), Oghogho et al,(2015a), Oghogho et al, (2015b), Oghogho, (2017, Oghogho et al, (2017), Oghogho et al, (2018). Among these researches, Oghogho et al, (2014b) and Oghogho, et al, (2015a) provided throughput CDF probability models based on different ranges of SNR observed.…”
mentioning
confidence: 99%